(untitled) - Barrion, A. T. (Wallingford, 1995)
This volume provides an illustrated guide that can be used by specialists and novices to identify these spiders. The majority of the species covered were collected from a diversity of habitats in the Philippines. The bulk of the book consists of keys to the identification of families, genera and species of Philippine spiders. Distribution maps for individual species and a classification scheme for Philippine riceland spiders are also provided. Overall, the work represents a major contribution to the literature for those interested in spiders or more generally in biological control and crop protection
Keywords: Spiders,Rice; Identification,Ecology; Philippines,Philippines